923. Rapid Emergence of Candida auris in the Chicago Region. (26th November 2018) - Kerins, Janna L; Tang, Angela S; Forsberg, Kaitlin; Jegede, Olufemi; Ealy, Michelle; Pacilli, Massimo; Welsh, Rory M; Murphy, Elizabeth B; Fealy, Amy; Walters, Maroya Spalding; Raczniak, Gregory; Vallabhaneni, Snigdha; et al.
Abstract: Background: In 2016, Candida auris was first reported in the United States, with 2 Illinois patients among the first cases. In response, the state and 3 Chicago-area health departments (HDs) investigated clinical cases and performed point prevalence surveys (PPSs) to identify colonized cases. Methods: Clinical cases had positive C. auris cultures obtained for clinical care; colonized cases had positive surveillance cultures during PPSs. In August 2016–January 2018, PPSs were performed in Chicago-area acute care hospital (ACH) intensive care units, long-term acute-care hospitals (LTACHs), and high-acuity floors of skilled nursing facilities (SNFs) and SNFs caring for ventilated patients (vSNFs). Facility and HD staff obtained composite axilla/groin swabs from assenting patients to detect colonization. Facilities with an epidemiologic link to a clinical case or a shared patient population with a facility housing a clinical case were prioritized for PPSs. Results: During May 2016–January 2018, Chicago-area facilities reported 24 clinical cases, including 10 bloodstream infections. HDs performed 33 PPSs at 20 facilities (5 ACHs, 5 LTACHs, 3 SNFs, and 7 vSNFs) during August 2016–January 2018. Of 1, 364 patients screened, 92 (6.7%) were colonized with C. auris ; 10 (50%) facilities had ≥1 colonized patient. A significantly higher proportion screened positive from September 2017 to January 2018 (84/822, 10.2%) than in August 2016–August 2017 (8/542, 1.5%; z -test P < 0.01). Prevalence of C. auris colonization was highest in vSNFs (median: 7.7%; range: 0%–43.3%), compared with ACHs (0%; 0%–6.3%), LTACHs (0%; 0%–14.3%), and SNFs (0%, 0%–1.5%). PPSs in vSNFs identified 91% (84/92) of colonized cases. Among 5 vSNFs with repeat PPSs, 4 had higher prevalence on repeat screening (median: 26.1%; range: 0%–43.3%) than at baseline (1.2%; 0%–17.0%). Conclusion: C. auris has rapidly emerged in the Chicago area. Increasing prevalence of C. auris colonization during repeat PPSs indicates transmission and amplification within vSNFs. To prevent spread, state and local HDs provided infection control recommendations, disseminated health alerts, and recommended placing vSNF patients from high-acuity floors on transmission-based precautions. Disclosures: All authors: No reported disclosures.